Magnetic core–shell Fe3O4@Cu2O and Fe3O4@Cu2O–Cu materials as catalysts for aerobic oxidation of benzylic alcohols assisted by TEMPO and N-methylimidazole. Issue 44 (10th July 2020) - Xu, Binyu; Senthilkumar, Samuthirarajan; Zhong, Wei; Shen, Zhongquan; Lu, Chunxin; Liu, Xiaoming
Abstract : Robust core–shell magnetic materials catalyse quantitatively the aerobic oxidation of a wide range of benzylic alcohols into corresponding aldehydes at room temperature showing excellent tolerance towards the substituents on the phenyl ring. Abstract : In this work, core–shell Fe3 O4 @Cu2 O and Fe3 O4 @Cu2 O–Cu nanomaterials for aerobic oxidation of benzylic alcohols are reported with 2, 2, 6, 6-tetramethylpiperidine- N -oxyl (TEMPO) and N -methylimidazole (NMI) as the co-catalysts. To anchor Cu2 O nanoparticles around the magnetic particles under solvothermal conditions, the magnetic material Fe3 O4 was modified by grafting a layer of l -lysine (l -Lys) to introduce –NH2 groups at the surface of the magnetic particles. With amine groups as the anchor, Cu(NO3 )2 was used to co-precipitate the desired Cu2 O by using ethylene glycol as the reducing agent. Prolonging the reaction time would lead to over-reduced forms of the magnetic materials in the presence of copper, Fe3 O4 @Cu2 O–Cu. The nanomaterials and its precursors were fully characterized by a variety of spectroscopic techniques. In combination with both TEMPO and NMI, these materials showed excellent catalytic activities in aerobic oxidation of benzylic alcohols under ambient conditions. For most of the benzylic alcohols, the conversion into aldehydes was nearly quantitative with aldehydes as the sole product. The materials were recyclable and robust. Up to 7 repeat runs, its activity dropped less than 10%. The over-reduced materials, Fe3 O4 @Cu2 O–Cu, exhibited slightly better performance in durability. The magnetic properties allowed easy separation after reaction by simply applying an external magnet.